Potensi Rebusan Kulit Buah Manggis Alami (Garcinia mangostana Linn) untuk Meningkatkan Aktivitas Mikrobisida Sel Neutrofil terhadap Streptococcus mutans (The Potency of Mangosteen Peel Infution (Garcinia mangostana L.) to Increase Neutrophil Microbicidal - Athiyah Naila Sakinah; Muhammad Nurul Amin; Purwanto . (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Neutrophils were part of leucocyte cells which dominate in blood circulation. When the microorganism entered the body, neutrophils kill it immediately. The steps that were migration, ingestion, swallowing, and microbicidal activity or intercellular killing. The contents of mangosteen peel is presumed to help neutrophils beat bacteria. Samples numbered 28 consist of 7 treatment groups, namely K 1 (negative control), K II (positive control), K III 100% MPI (Mangosteen Peel Infution), K IV 75% MPI, K V 50% MPI, K VI 25% MPI, and K VII 100% MPIwithout neutrophils. Isolated neutrophils exposed to MPI appropriate treatments groups above and then incubated for 3 hours. Subsequently exposed to S. mutans and incubated again for 3 hours. After that, the sample werecultured in BHI-A media and incubated for 1x24 hours. Furthermore, bacterial colonies were counted with a colony counter method. The result showed a significant difference between MPI treatment groups with control groups. The conclusion of this research is thenatural mangosteen peel infution hasthe potential to increase microbicidal activity of neutrophils and can act as an antibacterial. Keywords: mangosteen (Garcinia mangostana L.),microbicidal,neutrophils, S. mutans.